2015
DOI: 10.1007/s10336-015-1198-1
|View full text |Cite
|
Sign up to set email alerts
|

Access to water affects the condition dependency of nocturnal restlessness in Garden Warblers on a Mediterranean island stopover

Abstract: During migration, many songbirds encounter large ecological barriers, like deserts and seas that require substantial fuel to cross and can lead to dehydration during passage. If muscle is not catabolized to generate metabolic water, birds must seek free water on a subsequent stopover to replenish the water lost. Yet, no work has examined if birds crossing large migration barriers use access to free water in concert with energy or protein stores to make stopover decisions. We captured 61 free-living Garden Warb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Another recent study, on European blackbirds Turdus merula (Zúñiga et al), found that radio‐tracked wild migrants showed no increase in nocturnal activity until the night of departure from the breeding grounds, whereas captive birds slowly built up Zugunruhe over several weeks. The physiological and ecological mechanisms that affect alternations between flight and stopover mode are now under intense investigation, using both Zugunruhe and tracks of free‐flying birds (Fusani et al , , Goymann et al , Eikenaar et al , Skrip et al ). Dissection of the genetic and environmental regulators of migration will not only aid migration research, but also allow important advances for understanding how genes and environment interact to shape complex behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study, on European blackbirds Turdus merula (Zúñiga et al), found that radio‐tracked wild migrants showed no increase in nocturnal activity until the night of departure from the breeding grounds, whereas captive birds slowly built up Zugunruhe over several weeks. The physiological and ecological mechanisms that affect alternations between flight and stopover mode are now under intense investigation, using both Zugunruhe and tracks of free‐flying birds (Fusani et al , , Goymann et al , Eikenaar et al , Skrip et al ). Dissection of the genetic and environmental regulators of migration will not only aid migration research, but also allow important advances for understanding how genes and environment interact to shape complex behaviour.…”
Section: Discussionmentioning
confidence: 99%